Heritage in Harmony: Sustainable Pathways for Cultural Heritage Preservation in Chhindwara, Madhya Pradesh - Sanjeet Poddar,; Aditi Jharbade, (AG Volumes, 2026)
Cultural heritage plays a vital role in shaping the identity and continuity of societies, as it carries the memories of their historical and artistic past. Indian state, Madhya Pradesh is recognized for its rich cultural and historical significance, in this context preserving heritage while promoting sustainable tourism becomes a significant challenge. This paper examines at how this balance can be obtained in Chhindwara, the southernmost district of the state. It explores the intricate relationship between tradition, modernity, and economic development, highlighting the impact of tourism on the tribal culture and historical resources of the region. Through case studies and policy analysis, the study proposes a framework for integrating tourism growth with heritage conservation, ensuring long-term sustainability and community involvement.